Fingolimod mitigates synaptic deficits and psychosis‐like behavior in APP/PSEN1 mice - Josh M. Krivinko; Susan L. Erickson; Matthew L. MacDonald; Megan E. Garver; Robert A. Sweet (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract Introduction Current treatments for psychosis in Alzheimer's disease (AD), a syndrome characterized by more rapid deterioration and reduced synaptic protein abundance relative to non‐psychotic AD, are inadequate. Fingolimod, a currently US Food and Drug Administration (FDA)–approved pharmacotherapy for multiple sclerosis, alters synaptic protein expression and warrants preclinical appraisal as a candidate pharmacotherapy for psychosis in AD. Methods Presenilin and amyloid precursor protein transgenic mice (APPswe/PSEN1dE9) and wild‐type mice were randomized to fingolimod or saline for 7 days. Psychosis‐associated behaviors were quantified by open field testing, pre‐pulse inhibition of the acoustic startle response testing, and habituation of the acoustic startle response testing. Synaptic proteins were quantified by liquid chromatography/mass spectrometry in homogenate and postsynaptic density fractions. Results Fingolimod treatment increased the synaptic protein abundance in cortical homogenates and normalized psychosis‐associated behaviors in APPswe/PSEN1dE9 mice relative to saline. Mitochondrial‐related proteins were preferentially altered by fingolimod treatment and correlated with improvements in psychosis‐associated behaviors. Discussion Preclinical studies employing complementary psychosis‐associated behavioral assessments and proteomic evaluations across multiple AD‐related models are warranted to replicate the current study and further investigate fingolimod as a candidate treatment for psychosis in AD.